Soybean Cost-Return Budget in Western Kansas - O'Brien, Daniel M.; Dumler, Troy J.; Thompson, Curtis R.; Stockton, Roger (My University, 2002)
This publication contains information for a projected budged reflecting expected income and cost based on soybean production practices in western Kansas.
MF2366_2002_10
Keywords: MF2366; Economics; Crops; MF